Removal and adsorption kinetics of copper(II) ions from aqueous media on activated carbon in dynamic adsorption on a fixed-bed column - Mve Mfoumou, Charly; Tonda-Mikiéla, Pradel; Ngoye, Francis; Bouassa Mougnala, Spenseur; Mbouiti, Berthy Lionel; Feuya Tchouya, Guy Raymond (Comptes Rendus. Chimie)
Dynamic adsorption experiments on fixed-bed columns and adsorption kinetics studies of Cu2+ in aqueous media, under various experimental conditions, were carried out on activated carbon (AC) prepared using coconut shells from Franceville (Gabon). Results of dynamic adsorption experiments showed that particle size (x) of the column bed, flow rate (D) and bed height (h) influence adsorption capacities at saturation (Qsat) and removal percentages (E) of Cu2+ on the prepared AC. The best Qsat and E (52.52 mg/g and 55.02%, respectively) were obtained with 0.01 < x < 0.04 mm, D = 2 mL/min, and h = 3 cm, with Cu2+ concentration and pH constant at 250 mg/L and 6.5, respectively. The adsorption kinetic studies indicated that the Thomas model and pseudo-first-order kinetic model best describe the adsorption mechanisms of Cu2+ in our experimental conditions. On the other hand, in addition to reversible interactions (physisorption), it appeared that irreversible reactions (chemisorption) also took place on the surface of the adsorbent. Results obtained from the intraparticle kinetics model study indicated that intraparticle diffusion is not the limiting step in Cu2+ adsorption and that surface adsorption plays a predominant role.